Somebody with a little hammer : essays - Gaitskill, Mary, 1954- (Pantheon Books, 2017)
"Engaging, unusual essays written over the last two decades, on matters literary, social, cultural, and personal--from the explosive date rape debates of the '90s to the ubiquitous political adultery of the '00s, from Anton Chekhov to Celine Dion. Here is Mary Gaitskill the essayist: witty, direct, penetrating to the core of each issue, personality, or literary trope (On Updike: "It is as if [he] has entered a tiny window marked 'Rabbit,' and, by some inverse law, passed into a universe of energies both light and dark, expanded and contracted, infinite and workaday." On Elizabeth Wurtzell: "If this kooky, foot-stamping, self-loathing screed is meant to be, as it claims, a defense of 'difficult women,' i.e. women who 'write their own operating manuals' . . . all I can say is, bitches best duck and run for cover.") Gaitskill writes about the ridiculous and poetic ambition of Norman Mailer, about the socio-sexual cataclysm embodied by porn star Linda Lovelace, and, in the deceptively titled "Lost Cat," about how power and race can warp the most innocent and intimate of relationships. Appearing in chronological order, the essays offer their thoughts and reactions, always with the heat-seeking, revelatory understanding for which we value the author's fiction"--